2022
DOI: 10.3389/fmed.2022.888408
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profile of SARS-CoV-2 Omicron variant and its correlation with disease severity in Rajasthan

Abstract: BackgroundOmicron, a new variant of Severe Acute Respiratory Syndrome-Coronavirus 2 (SARS-CoV-2), was first detected in November 2021. This was believed to be highly transmissible and was reported to evade immunity. As a result, an urgent need was felt to screen all positive samples so as to rapidly identify Omicron cases and isolate them to prevent the spread of infection. Genomic surveillance of SARS-CoV-2 was planned to correlate disease severity with the genomic profile.MethodsAll the SARS-CoV-2 positive c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
3
6
0
Order By: Relevance
“…A growing number of reports indicated that the Omicron-associated COVID-19 disease was less severe than the Delta-associated COVID-19 disease, resulting in more asymptomatic patients [30,31] . A study from India showed that the majority of patients infected with Omicron were asymptomatic (56.7%) [32] , consistent with our study. The Faroe Islands study reported that in over half the cases, patients assessed their illness as asymptomatic or mild [33] .…”
Section: Discussionsupporting
confidence: 92%
“…A growing number of reports indicated that the Omicron-associated COVID-19 disease was less severe than the Delta-associated COVID-19 disease, resulting in more asymptomatic patients [30,31] . A study from India showed that the majority of patients infected with Omicron were asymptomatic (56.7%) [32] , consistent with our study. The Faroe Islands study reported that in over half the cases, patients assessed their illness as asymptomatic or mild [33] .…”
Section: Discussionsupporting
confidence: 92%
“…A growing number of reports indicated that the Omicron-associated COVID-19 disease was less severe than the Delta-associated COVID-19 disease, resulting in more asymptomatic patients. 30 , 31 A study from India showed that the majority of patients infected with Omicron were asymptomatic (56.7%), 32 consistent with our study. The Faroe Islands study reported that in over half the cases, patients assessed their illness as asymptomatic or mild.…”
Section: Discussionsupporting
confidence: 90%
“…Library preparation was done by Ion AmpliSeq library kit plus, template preparation, enrichment and chip loading was done on Ion Chef system (Life Technologies) and loaded chips were sequenced on the Ion torrent S5 system(Life Technologies). NGS data analysis was done as described previously [10]. The FASTA files obtained on sequencing were aligned withWuhan-Hu-1/2019 (genbank: MN908947) as reference using Nextclade (https://clades.Nextstrain.org).…”
Section: Methodsmentioning
confidence: 99%